Randomized study on the effectiveness of nomegestrol acetate plus 17β-estradiol oral contraceptive versus dienogest oral pill in women with suspected endometriosis‑associated chronic pelvic pain - Salvatore Caruso; Antonio Cianci; Marco Iraci Sareri; Marco Panella; Giuseppe Caruso; Stefano Cianci (BMC, 2022)
Abstract Background To evaluate the effects of a combined oral contraceptive containing 1.5 mg 17b-estradiol (E2) and 2.5 mg nomegestrol acetate (NOMAC) or 2 mg/daily dienogest (DNG) oral progestin on endometriosis-associated chronic pelvic pain (CPP) and on the quality of life (QoL) and sexual function, by a randomized study design. Methods The E2/NOMAC group and DNG group included 99 and 98 women, respectively. The levels of CPP were measured by the visual analogic scale (VAS). The QoL scores were investigated by the Short Form-36 questionnaire (SF-36). Finally, sexual function was studied using the Female Sexual Function Index (FSFI), while sexual distress was studied by the Female Sexual Distress Scale (FSDS). The study had 3, 6 and 12-month follow-ups. Results The intra-group analysis showed an improvement of the VAS score from baseline to the 12-month follow-up in the women of both groups (p < 0.001). The inter-group comparison showed a similar improvement of CPP (p = 0.06). Women on DNG had better SF-36 somatic (p < 0.01) and FSFI scores (p < 0.006) than women on E2/NOMAC at the 6- and 12-month follow-ups. Conclusions The results support the efficacy of both hormonal treatments, even if DNG was more effective than E2/NOMAC in a limited intergroup comparison.